2019
DOI: 10.15578/bawal.11.3.2019.161-173
|View full text |Cite
|
Sign up to set email alerts
|

PERIKANAN TUNA SIRIP KUNING (Thunnus albacares Bonnaterre, 1788) PADA ARMADA TONDA DI SAMUDERA HINDIA SELATAN JAWA

Abstract: Tuna sirip kuning (Thunnus albacares) merupakan hasil tangkapan terbanyak dibandingkan dengan jenis tuna lainnya di Indonesia. Ketersediaan stok tuna sirip kuning di Samudra Hindia, pada saat ini, diperkirakan dalam keadaan lebih tangkap. Oleh karena itu, pengelolaan secara tepat dan bertanggungjawab penting dilakukan untuk melindungi spesies tuna, salah satu caranya dengan mengkaji alat tangkap yang digunakan. Tulisan ini bertujuan untuk mengungkapkan produktivitas dan hasil tangkapan armada tonda, serta stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
5
0
2
Order By: Relevance
“…Although the parameters a derived from our study were consistent with studies conducted in other areas, b values were slightly lower compared to the estimates from Pratibha and Rammohan [17] and Jamitko et al [18] . Nevertheless, the linear regressions values (b) for yellowfin tuna caught in our study align with those reported in other areas, such as the Southeast coast of India [23] and West Java, Indonesia [16,24,25] . The exponential coefficient (b) in the length-weight relationship varies among species due to environmental factors.…”
Section: ~ 96 ~supporting
confidence: 90%
See 2 more Smart Citations
“…Although the parameters a derived from our study were consistent with studies conducted in other areas, b values were slightly lower compared to the estimates from Pratibha and Rammohan [17] and Jamitko et al [18] . Nevertheless, the linear regressions values (b) for yellowfin tuna caught in our study align with those reported in other areas, such as the Southeast coast of India [23] and West Java, Indonesia [16,24,25] . The exponential coefficient (b) in the length-weight relationship varies among species due to environmental factors.…”
Section: ~ 96 ~supporting
confidence: 90%
“…The length frequency distribution of yellowfin was 20-170 cm with a weight range of 0.2-82 kg. Meanwhile, a study from Molluca Sea, Indonesia showed a length range of yellowfin from 85-174 cm and a weight range of 10-75 kg [15] , length range of yellowfin in West Java, Indonesia from 23-168 cm [16] .…”
Section: Results and Discussion 31 Length-weight Frequency Distributi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the yellowfin tuna caught in southern Java are fish that have not been caught because they are less than 100 cmFL in size. The structure of the length of the yellowfin tuna caught the longer to the east, the longer the size [14]. Most of the yellowfin tuna landed by purse seine were of a smaller size than predicted, YFT caught in the Indian Ocean are in the range of length 131-140 cm and weight 46-50 kg [15], and in the range of length 23-168 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the length of the yellowfin tuna caught the longer to the east, the longer the size [14]. Most of the yellowfin tuna landed by purse seine were of a smaller size than predicted, YFT caught in the Indian Ocean are in the range of length 131-140 cm and weight 46-50 kg [15], and in the range of length 23-168 [14]. The fish suitable for catching is the size of the fish at first gonad maturity (length at first maturity = Lm) [16].…”
Section: Discussionmentioning
confidence: 99%